Features of Comorbid AnxietyDepression Disorders and Personal Changes in Type 2 Diabetes Mellitus (Eurasian Research Bulletin, 2023)
This article describes the polymorphism of mental disorders in patients seeking help in medical institutions of a somatic profile, is high. According to the WHO, more than half of patients suffering from moderate to severe somatic diseases have some kind of mental disorder. High prevalence, chronic course of the disease, polyetiology, polymorphism of somatic and mental disorders make diabetes mellitus the most suitable model for the study and systematization of mental disorders in somatic patients.